Tripla hélice "desmembrada" : a dificuldade da inovação no Brasil - Rocha, Roberto Oliveira (2014)
In spite of being an opening concept, innovation has fomented useful theoretical discussions. One of the most applied approaches is the `Triple Helix´ model, which identifies societies with higher ability of promoting innovative practices and environments as those where the helixes `Government´, `Universities´ and `Industry´ are better articulated, in a horizontal relation. What it follows is a work that aims to problematize that discussion to Brazilian context, pointing the existence of socio-political features which inhibit the interconnection among these main participants of the process. First, we take into account some aspects connected to Brazilian constitution, which reveals into a developmentalism logic. Later, we discuss the national technic-scientific activities, analyzing them based on Triple Helix theory and general theoretical contributions. And, as an attempt to delineate this relation more clearly, the next step was chosen looking at a more restrictive and specific object: the RHAE-Pesquisador na Empresa program, which confirmed the difficulties of a consolidation of this intended articulation among those helixes. In this way, we undertake a quite wide although needful sociological research, once the chosen thematic has a complex dynamics.